Complex associations between periodontitis and cerebrovascular disease - Cristina Andrada Costea; Iulia Cristina Micu; Andrada Șoancă; Ștefan Ioan Stratul; Andreea Ciurea; Alexandra Roman (Amaltea Medical Publishing House, 2020)
Aim. All the data from the literature suggests a strong association between periodontitis and stroke, but the conclusions were heterogeneous. Also, longitudinal studies report an increased risk for stroke in patients with periodontitis. This article aimed to investigate through the most recent evidence, the relation of association between periodontitis and stroke and its clinical significance. Methods. A well structured strategy was applied to Pubmed database. The last research was performed in 1st of July 2020. Results. From all 490 articles initially selected only 18 corresponded with the inclusion criteria from this review. Periodontitis was associated with stroke and it also represented an independent risk factor for ischemic stroke. The periodontal treatment may reduce the risk for primary stroke or recurrent stroke. Conclusions. The data presented in this article support the relation of association between periodontitis and stroke. Oral health and the treatment of infectious and inflammatory oral conditions are very important not only for maintaining oral health but also for maintaining systemic health.